Fabrication and Characterization of Fe-Doped In2O3 Dilute Magnetic Semiconducting Nanowires**Supported by the National Basic Research Program of China under Grant Nos 2014CB921101, 2014CB921103 and 2013CB922103, the National Natural Science Foundation of China under Grant Nos 11274003, 61176088 and 61274102, the Program for the New Century Excellent Talents in University under Grant No NCET-11-0240, the PAPD Project, and the Fundamental Research Funds for the Central Universities. (March 2015) - Zhang, Jun-Ran; Wu, Zhen-Yao; Liu, Yu-Jie; Lv, Zhan-Peng; Niu, Wei; Wang, Xue-Feng; Du, Jun; Liu, Wen-Qing; Zhang, Rong; Xu, Yong-Bing
<x content-type="archive" xml:space="preserve">Abstract</x> Fe-doped In2O3 dilute magnetic semiconducting nanowires are fabricated on Au-deposited Si substrates by the chemical vapor deposition technique. It is confirmed by energy dispersive x-ray spectroscopy (EDS), x-ray photoelectron spectroscopy (XPS) and Raman spectroscopy that Fe has been successfully doped into lattices of In2O3 nanowires. The EDS measurements reveal a large amount of oxygen vacancies existing in the Fe-doped In2O3 nanowires. The Fe dopant exists as a mixture of Fe2+ and Fe3+, as revealed by the XPS. The origin of room-temperature ferromagnetism in Fe-doped In2O3 nanowires is explained by the bound magnetic polaron model.